(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
The purpose of this paper is to analyze the behavior of the Nicaraguan university community during the second half of the triumph of the Sandinista Popular Revolution. Many times we have talked about the historical struggles of the student movement, the antagonism to the Somoza dictatorship, the defense of the Revolution, the struggle for 6%, constitutional that was not only seen in covering tariffs, and payment to teachers , but it went beyond. An economic material base was sought that would allow the survival of the University in a fair, rational, participatory, democratic and accessible way to the people.